Minimizing the cost by effective utilization of resources which yields better profits for government organizations in a less interval of time - Nanda Krishna, Ch.; Ramesh, M.; M. Suneetha, Dr. (International Journal of Engineering and Technology, 2018)
Minimizing the cost and utilization of resources in an efficient manner helps any organization in its progress that is growth of the organization. This paper gives an optimized solution for reducing the cost of resources in government services of Transportation. If the data is structured can use any one of the Relational Database Management Systems (RDBMS), if the data is unstructured or semi-structured we can use hadoop for processing the data and analyze the data which is processed by using R. Strategic decision making can be made by the end results that we get from the visualizations of R-Language in-order to get better insights of the business and better decisions can be taken for better growth of the organization.Â Â